О современном состоянии обеспеченности пищей черноморского шпрота - Никольский, В.Н.; Шульман, Г.Е.; Юнева, Т.В.; Щепкина, А.М.; Ивлева, Е.В.; Бат, Л.; Кидейш, A. (Видавничий дім "Академперіодика" НАН України, 2007)
The sprat fat content in the northern part of the Black Sea at the end of its feeding period (June–August) during 2002–2005 is studied. In general, the sprat fat content demonstrates a dramatic decrease last years in relation to the mean values defined in 1960–2001. These results indicate a very bad nutritional condition of sprat stocks in the last years, which is obviously related to the worsening of the food supply. The last can be related to the high water temperature which occurs in the Black Sea last years.